2001
DOI: 10.1161/hh2401.100818
|View full text |Cite
|
Sign up to set email alerts
|

Rectification of the Background Potassium Current

Abstract: Abstract-Ventricular fibrillation (VF) is the leading cause of sudden cardiac death. Yet, the mechanisms of VF remain elusive. Pixel-by-pixel spectral analysis of optical signals was carried out in video imaging experiments using a potentiometric dye in the Langendorff-perfused guinea pig heart. Dominant frequencies (peak with maximal power) were distributed throughout the ventricles in clearly demarcated domains. The fastest domain (25 to 32 Hz) was always on the anterior left ventricular (LV) wall and was sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(62 citation statements)
references
References 36 publications
(34 reference statements)
4
56
2
Order By: Relevance
“…Some areas excite at higher rates than others and the DFs organize in clearly demarcated domains. As demonstrated in hearts from guinea pigs and mice (4,13), the frequency of the vortices, or their rotation period (1/frequency), closely matched the frequency of fibrillation or cycle length calculated from the DF maps or the ECG. However, please note that the highest DF domain decreases with increasing body size (mouse, 38 Hz; guinea pig, 26 Hz; rabbit, 15 Hz; human, 6.8 Hz).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Some areas excite at higher rates than others and the DFs organize in clearly demarcated domains. As demonstrated in hearts from guinea pigs and mice (4,13), the frequency of the vortices, or their rotation period (1/frequency), closely matched the frequency of fibrillation or cycle length calculated from the DF maps or the ECG. However, please note that the highest DF domain decreases with increasing body size (mouse, 38 Hz; guinea pig, 26 Hz; rabbit, 15 Hz; human, 6.8 Hz).…”
Section: Resultssupporting
confidence: 63%
“…One school of thought suggests that, during fibrillation, the electrical waves propagate through the ventricles at random, with no underlying deterministic organization (2,3). Others postulate that, although VF is complex, it is maintained by organized electrical vortices, called ''rotors,'' that spin at exceedingly high frequencies around a central core region (4). Waves shed by the rotors take a spiral shape near the core but may turn into disorganized patterns of propagation known as ''fibrillatory conduction'' in the rotor's periphery (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…by one stable high frequency source mother rotor and complex VF patterns are the result of multiple breaks of the waves from this source at heterogeneities of the heart [3]. The multiple wavelet hypothesis explains VF by breakup of spiral waves due to dynamical or anatomical heterogeneity [4,5].…”
mentioning
confidence: 99%
“…13 The reasons for the modification of the ionic model from its original version are the following. A singlecell electrophysiological study by Samie et al 14 have shown that LV myocardial cells have larger background potassium current as compared to RV cells. The study by Samie et al incorporated spline functions in the LR1 model (available at the journal website) to represent the experimental current-voltage relationship the authors obtained for isolated LV and RV cells.…”
Section: Representation Of Ionic Currents and Membrane Electroporamentioning
confidence: 99%